2015
DOI: 10.1074/jbc.m114.608174
|View full text |Cite
|
Sign up to set email alerts
|

Cohen Syndrome-associated Protein COH1 Physically and Functionally Interacts with the Small GTPase RAB6 at the Golgi Complex and Directs Neurite Outgrowth

Abstract: Background: COH1 is a peripheral membrane protein that is required for Golgi complex integrity and function. Results: Association of COH1 with the Golgi complex is mediated by its interaction with RAB6 and is required for neurite outgrowth. Conclusion: COH1 acts as downstream effector protein of RAB6. Significance: Defective neuronal outgrowth due to loss of COH1 contributes to the neurological impairments found in Cohen syndrome patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 39 publications
5
61
0
2
Order By: Relevance
“…VPS13B mutations cause Cohen syndrome, a developmental disorder characterized by mental retardation, microcephaly and facial dysmorphisms [9]. VPS13B has been reported to be a Rab6 effector that controls Golgi integrity [10,11]. VPS13C mutations have recently been described to cause autosomal-recessive early-onset Parkinson’s disease, probably by alteration of mitochondrial morphology and function [12].…”
Section: Introductionmentioning
confidence: 99%
“…VPS13B mutations cause Cohen syndrome, a developmental disorder characterized by mental retardation, microcephaly and facial dysmorphisms [9]. VPS13B has been reported to be a Rab6 effector that controls Golgi integrity [10,11]. VPS13C mutations have recently been described to cause autosomal-recessive early-onset Parkinson’s disease, probably by alteration of mitochondrial morphology and function [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wenke Seifert et al have reported COH1 regulates the differentiation and integration of neurons into a functional network. Reduced COH1 attachment to the Golgi membrane will inhibits efficient polarization and targeted membrane transport toward the developing axon (Seifert et al, 2015). Laurence Duplomb et al have verified that VPS13B plays a major role in the function of the Golgi apparatus associated with major alterations in protein glycosylation in CS patients with VPS13B mutations (Duplomb et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…If human VPS13 proteins have evolved different localization mechanisms to target distinct contact sites, the VAB domains of some paralogs may have lost their adaptor binding function. This could be true for VPS13B, which has a poorly conserved VAB domain and instead localizes to Golgi membranes through its C-terminus (52). The divergent VAB domain of VPS13B has serine residues in the place of conserved asparagines in the 2 nd and 3 rd VAB domain repeats.…”
Section: The Role Of Vab Domain In Human Vps13 Proteinsmentioning
confidence: 99%